SAFEGUARD : SOSIALISASI KEAMANAN TRANSAKSI ONLINE UNTUK MENANGGULANGI KEJAHATAN KEUANGAN PADA PELAKU UMKM KOTA PANGKALPINANG - Zukhri, Nizwan; Anggita, Wenni; Manik, Jeanne Darc Noviayanti; Wahyudin, Nanang (Jurnal Abdi Insani, 2025)
The advancement of digital technology has brought significant transformation to the business world, including for Micro, Small, and Medium Enterprises (MSMEs). In Pangkalpinang City, MSMEs have begun utilizing digital platforms to expand their market reach and increase sales volume. However, on the other hand, the high activity of online transactions also opens opportunities for the emergence of digital financial crimes such as phishing, scams, and social engineering. According to data from the Pangkalpinang Resort Police, there has been a 25% increase in reported cases of digital fraud targeting MSME actors over the past year. The lack of understanding about digital security is a major factor making MSMEs vulnerable to becoming victims. Therefore, this community service activity is present as an effort to enhance the digital security literacy of MSME actors in Pangkalpinang City in facing the threats of online transaction crimes. This activity was designed with a participatory and collaborative approach, involving various stakeholders such as academics, local government, and digital security practitioners. The methods used include interactive outreach, simulation of digital fraud cases, technical training on platform security, and group-based mentoring. The participants consisted of 40 MSME actors from various sectors, including culinary, handicrafts, and services. Evaluation results showed a 78% improvement in participants' understanding based on pre-test and post-test assessments, with participants able to identify fraud modes such as phishing, scams, and social engineering. Furthermore, the formation of a WhatsApp group, the "Digital Safeguard MSME" application, and the Pangkalpinang MSME Digital Security Task Force serve as vehicles for program sustainability. This activity concludes that participatory and collaborative educational approaches with stakeholders are effective in enhancing the digital resilience of MSMEs. It is recommended to periodically expand training programs and integrate digital security policies into regional MSME development strategies.